El entrecruzamiento de la historia y la ficción en La ceiba de la memoria de Roberto Burgos Cantor a través de la metaficción historiográfica - Pérez Cuestas, Luis Fernando (Universidad Pedagógica y Tecnológica de Colombia. Facultad de Ciencias de la Educación, 2024)
Eng: This degree work analyzes the intersection of history and fiction that occurs in the novel La ceiba de la memoria by the Colombian writer Roberto Burgos Cantor, based on the concept of Historiographical Metafiction developed by theorist Linda Hutcheon. This concept assumes three strategies that are evident in the novel: parody as a critical exercise of an exposed historical reality, polyphony and heteroglossia as discursive strategies to assume a historical discourse that lacks absolute truths, and metafiction as a self-awareness of the creative process not only of the author, but also of the protagonists themselves and of the history. These strategies of historiographical metafiction that occur at the crossroads between history and fiction make possible an awareness, not only about the reality of African slavery and Jewish genocide, but also about our human nature and the relationship with the other.